Delta-sigma modulator based compact sensor signal acquisition front-end system. (April 2020) - Basu, Joydeep; Mandal, Pradip
Abstract: The proposed delta-sigma modulator (ΔΣM) based signal acquisition architecture uses a differential difference amplifier (DDA) customized for dual purpose roles, namely as instrumentation amplifier and as integrator of ΔΣM. The DDA also provides balanced high input impedance for signal from sensors. Further, programmable input amplification is obtained by adjustment of ΔΣM feedback voltage. Implementation of other functionalities, such as filtering and digitization have also been incorporated. At circuit level, a difference of transconductance of DDA input pairs has been proposed to reduce the effect of input resistor thermal noise of front-end R–C integrator of the ΔΣM. Besides, chopping has been used for minimizing effect of flicker noise. The resulting architecture is an aggregation of functions of entire signal acquisition system within the single block of ΔΣM, and is useful for a multitude of dc-to-medium frequency sensing and similar applications that require high precision at reduced size and power. An implementation of this in 0.18- μ m CMOS process has been presented, yielding a simulated peak signal-to-noise ratio of 80 ​dB and dynamic range of 109 ​dBFS in an input signal band of 1 ​kHz while consuming 100 ​μW of power; with the measured signal-to-noise ratio being lower by about 9 ​dB.